DS 110: Proceedings of the 23rd International Conference on Engineering and Product Design Education (EPDE 2021) 2021
DOI: 10.35199/epde.2021.7
|View full text |Cite
|
Sign up to set email alerts
|

Have You Felt Blue or Red? A Colour-Based Tool for Culturally Plural Teams

Abstract: The extensive practice of collaborative design-based learning and the increasing cultural plurality of design courses in Design Education is becoming relevant. Students' critical reflection on teamwork experience through structured activities of self-, peer and group evaluation can provide a space for students to ask themselves pertinent questions and to discuss together with the team about each one's reflections. A guided sharing of personal perspectives on teamwork reveals to students the existence of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Consequently, peers, self and the community should become an authority and knowledge source beyond the teacher [1]. Previous research in the situated context conducted by the authors showed that teambased instructional projects support these shifts at a team level but might also favour a competitive interteam environment [2]. Such competition often hinders collaboration and knowledge exchange at a class level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, peers, self and the community should become an authority and knowledge source beyond the teacher [1]. Previous research in the situated context conducted by the authors showed that teambased instructional projects support these shifts at a team level but might also favour a competitive interteam environment [2]. Such competition often hinders collaboration and knowledge exchange at a class level.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in school systems where grades are less relevant, students approach projects more casually, leading to self-directed and peer learning. While emphasising evaluation encourages constant commitment, it may discourage risk-taking and knowledge exchange with other teams in the class [2]. Given this contextual observation, the paper aims to present a case study of an instructional design project aimed at reshaping the interactions between teams within a team-based design studio from a highly competitive inter-group climate to a more collaborative one.…”
Section: Introductionmentioning
confidence: 99%